A State of Technology Use in English Language Learning at SMAN 1 Suliki - Novianti, Anggi; Wahyuni, Delvi (Universitas Negeri Padang, 2024)
The lack of the technology use is one of the crucial aspects that form two camps of students who have privilege and expertise in using technology and students who have less opportunity to use technology in English language learning environment. This study aimed to find out student students’ perception on digital divide in English language learning at SMAN 1 Suliki. Furthermore, this research conducted by using descriptive method. There were 91 students of SMAN 1 Suliki that were chosen as the sample by using simple random sampling technique. Quantitative analyses were employed in this research using liker scale approach to measure the questionnaire and calculated the mean score. From the data analysis of the questionnaire, the writer found that the mean score of the students’ perception on digital divide was in a good or positive perception category which means that most all of the students get the beneficial of the use of the technology in English language learning. In addition, almost all of the students agree that the use of the technology is beneficial in English language learning.Keywords: Technology, ICT, English Language Learning